2008
DOI: 10.1093/nar/gkm1079
|View full text |Cite
|
Sign up to set email alerts
|

Secondary DNA structure formation for Hoxb9 promoter and identification of its specific binding protein

Abstract: Hox genes determine anterior–posterior specificity of an animal body. In mammals, these genes map onto four chromosomal loci in a clustered manner, and their expression is regulated in a coordinated manner according to their chromosomal structure. In the present study, we analysed the Hoxb9 promoter and found that promoter activity in cultured cells is linked to secondary structure formation of promoter DNA. In nuclear extracts, we also detected binding activity specific for secondary-structured DNA. We succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
3
6
0
Order By: Relevance
“…Based on these observations, and considering that KDM2B also encodes a ZF-CxxC domain, we set out to examine whether KDM2B had a similar role to KDM2A in binding non-methylated DNA and CGIs (Blackledge et al, 2010). In agreement with previous work, recombinant KDM2B was found to bind non-methylated DNA in vitro (Koyama-Nasu et al, 2007; Yamagishi et al, 2008; Blackledge et al, 2012) in a manner that is comparable to that of KDM2A (Figure 1A,B). This suggests that KDM2B, like KDM2A, may recognize non-methylated DNA in vivo and bind CGI elements.…”
Section: Resultssupporting
confidence: 92%
“…Based on these observations, and considering that KDM2B also encodes a ZF-CxxC domain, we set out to examine whether KDM2B had a similar role to KDM2A in binding non-methylated DNA and CGIs (Blackledge et al, 2010). In agreement with previous work, recombinant KDM2B was found to bind non-methylated DNA in vitro (Koyama-Nasu et al, 2007; Yamagishi et al, 2008; Blackledge et al, 2012) in a manner that is comparable to that of KDM2A (Figure 1A,B). This suggests that KDM2B, like KDM2A, may recognize non-methylated DNA in vivo and bind CGI elements.…”
Section: Resultssupporting
confidence: 92%
“…The changes observed in the expression of Aass, Nqo1, Prdx4, and Serpinb1b were sufficient to induce the oxidative-stress phenotype of Ndy1 overexpression. The data in this report showing that Ndy1 functions as an activator of transcription are in agreement with recently published data showing that Ndy1 promotes the transcriptional activation of the Hoxd1 gene (47). Other studies, however, have shown that Ndy1 functions as a transcriptional repressor (8,10,39).…”
Section: Discussionsupporting
confidence: 93%
“…F-box proteins function as components of SCF-type E3 ubiquitin ligase complexes and may participate in co-repressor complexes (Gearhart et al 2006). The presence of a histone demethylase activity in FBXL10 was shown to be important for regulation of cell senescence and transcription of rRNAs (Jin et al 2004, Takeuchi et al 2006, Frescas et al 2007, He et al 2008, Pfau et al 2008, Yamagishi et al 2008. In our experiments, truncated versions of FBXL10 gene were recovered lacking the 5 0 -terminal part encoding the demethylase domain.…”
Section: Discussionmentioning
confidence: 76%